2010
DOI: 10.1002/chem.200902233
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Solvent on the Mechanism of Proton Transfer to Hydride Complexes: The Case of the [W3PdS4H3(dmpe)3(CO)]+ Cubane Cluster

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
2
13
0
Order By: Relevance
“…In this context, the combination of stopped‐flow NMR spectroscopy and mass spectrometry techniques represents a powerful approach for the analysis of the solution behaviour and the kinetics of interconversion between different chemical species. This is illustrated clearly by our mechanistic studies on the proton‐transfer reactions between diphosphino trinuclear M 3 S 4 (M = Mo, W) hydride clusters and acids, which support the initial formation of dihydrogen‐bonded adducts that then evolve to substitution products with H 2 release . As previously mentioned, this finding led us to investigate the catalytic activity of these systems in the reduction of nitro derivatives to obtain amines selectively in high yields …”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…In this context, the combination of stopped‐flow NMR spectroscopy and mass spectrometry techniques represents a powerful approach for the analysis of the solution behaviour and the kinetics of interconversion between different chemical species. This is illustrated clearly by our mechanistic studies on the proton‐transfer reactions between diphosphino trinuclear M 3 S 4 (M = Mo, W) hydride clusters and acids, which support the initial formation of dihydrogen‐bonded adducts that then evolve to substitution products with H 2 release . As previously mentioned, this finding led us to investigate the catalytic activity of these systems in the reduction of nitro derivatives to obtain amines selectively in high yields …”
Section: Introductionsupporting
confidence: 75%
“…DFT calculations were used to obtain further insights into the reactivity of 1 + towards both reagents (see Computational Details). For simplicity, the computations focused on the processes that occur at a single metal centre, an approach that has proven useful in previous studies of the reactivities of cuboidal clusters , , , . The computations started with the optimization of the hypothetical species resulting from the coordination of OH – ions and Et 3 N to the species resulting from the dissociation of the Br – ligands in 1 + , that is, [W 3 S 4 Br 2 (edpp) 3 ] 2+ .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, we have recently found that ligand substitutions in this kind of cluster can go also through a particular associative mechanism in which the excess of electron density caused by attack by the entering ligand is compensated by reorganization of the cluster core, without dissociation of the leaving ligand (see Figure 9). 4,17 The entering Y ligand coordinates to the metal centre without dissociation of the leaving X, the process being accompanied of structural changes in the cluster core. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 …”
Section: The Kinetics Of Substitution Reactionsmentioning
confidence: 99%
“…For example, mechanistic studies on the proton transfer reaction between trinuclear diphosphino M 3 S 4 (M= Mo, W) cluster hydrides and acids support the formation of dihydrogenbonded adducts by acid attack to the hydrides in the X sites of Figure 2 as intermediates or transition states. 4,[15][16][17] This finding led us to investigate the catalytic reduction of organic substrates mediated by these trimetallic hydrides. In collaboration with Beller`s group, we found that trinuclear Mo 3 S 4 hydrides functionalized with outer diphosphane ligands are excellent catalysts for the highly selective reduction of nitroarenes to the corresponding anilines.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In addition, along the years we have achieved a full knowledge of the kinetics of diphosphine molybdenum and tungsten M 3 Q 4 (Q=S, Se) hydrides versus acids. [6][7][8] An understanding of the consequences that result from replacing outer diphosphine by aminophosphine ligands may provide key information on the mechanistic details behind bifunctional metal/NÀ H catalysis.…”
Section: Introductionmentioning
confidence: 99%